Juridical Review On Administrative Law And E-Ktp Implementation Practices At The District Level In Connection With Law Number 23 Of 2006 - Sufmi Dasco Ahmad (Jurnal Mantik, 2021)
Public service is a strategic point in the development of good governance. One of the tasks of the government is the service of making identity cards (KTP) and in its implementation it is closely related to the rights of every Indonesian citizen. As stated by Masrin, one of the general tasks of government is the population administration system, which in its implementation is closely related to civil rights or civil rights of the population. This research is descriptive analytical research, namely research that conveys an overview of the existing facts supported by applicable and applied provisions. The method used is the Normative Juridical Approach Method, namely the Legal Research Method of Library/Secondary Data. In this study using a qualitative method which aims that the existing data is then analyzed qualitatively based on the existing statutory regulations as Positive Legal Norms so that it does not use numbers or formulas and statistics. Gradually improving the population administration management system is always being improved, in order to avoid deviations in which the government has implemented a method, namely the Population Administration Information System (SIAK), the implementation of the Population Administration System (SIAK) which requires a National Population Identification Number (NIK) nationally, with the issuance of a National Population Registration Number. Each person's National Identity Number (NIK) will not be the same until the holder of the Population Identification Number (NIK) dies. It is hoped that the Population and Civil Registry Office will continue to improve and optimize evenly and overall, related to the communication system carried out, human resources, disposition and bureaucratic structure so that the administration of population administration can be more effective and equitable at various levels of society in the future.